Overhead analysis of location-aware two-phase coding multi-channel MAC protocol (LA-TPCMMP) for MANETs - Zhang, Lili (2011)
We present a novel location-aware multi-channel medium access control (MAC) protocol for large-scale dense mobile ad hoc networks (MANETs) based on a scalable two-phase coding scheme, where the first-phase code is used to differentiate adjacent cells and the second-phase code is employed to distinguish nodes in one specific cell. It eliminates the hidden terminal problem (HTP) during data transmission without requiring periodical exchange of neighborhood information. Furthermore, we introduce a collision resolution mechanism in the control channel. We analyze the performance of the proposed protocol in terms of control overhead. Its theoretical results are confirmed by simulations and it is demonstrated that the new protocol significantly outperforms the classical code division multiple access (CDMA) based multi-channel MAC protocols.